Chlorhexidine allergy in four specialist allergy centres in the United Kingdom, 2009–13: clinical features and diagnostic tests. (13th March 2017) - Egner, W.; Helbert, M.; Sargur, R.; Swallow, K.; Harper, N.; Garcez, T.; Savic, S.; Savic, L.; Eren, E.
Summary: We describe an observational survey of diagnostic pathways in 104 patients attending four specialist allergy clinics in the United Kingdom following perioperative hypersensitivity reactions to chlorhexidine reactions. The majority were life‐threatening. Men undergoing urological or cardiothoracic surgery predominated. Skin prick testing and specific immunoglobulin (sIg)E testing were the most common tests used for diagnosis. Fifty‐three per cent of diagnoses were made on the basis of a single positive test. Where multiple tests were performed the sensitivity of intradermal, basophil activation and skin prick testing was 68% (50–86%), 50% (10–90%) and 35% (17–55%), respectively. Seven per cent were negative on screening tests initially, and 12 cases were only positive for a single test despite multiple testing. Intradermal tests appeared most sensitive in this context. Additional sensitization to other substances used perioperatively, particularly neuromuscular blocking agents (NMBA), was found in 28 patients, emphasizing the need to test for possible allergy to all drugs to which the patient was exposed even where chlorhexidine is positive. Abstract : Perioperative chlorhexidine allergy in the UK is often severe. Investigation is complicated by multiple test positivity to potential culprit agents and false negativity in screening tests to chlorhexidine. Testing by multiple modalities including IDT is useful where initial testing is negative.